2021
DOI: 10.3389/fpsyt.2021.731297
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on the General Mental Health in Sweden: No Observed Changes in the Dispensed Amount of Common Psychotropic Medications in the Region of Scania

Abstract: Some first investigations have focused on the consequences of the COVID-19 pandemic for the general mental health after its outbreak in 2020. According to multiple self-reporting surveys, symptoms of stress, anxiety, and depression have risen worldwide. Even some studies based on health care records start to be published, providing more objective and statistically reliable results. Additionally, concerns have been raised, to what extend the access to mental health care has been compromised by the COVID-19 outb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…On the contrary, other studies found an initial reduction of AD use during the peak of the first wave followed by an increased use in the subsequent periods [21]. Finally, some authors reported a non-significant change in psychotropic medication dispensing, including ADs, during the outbreak [22]. To the best of our knowledge, evidence on the impact of lockdowns on AD use in Italy is still scant and deserves careful evaluation.…”
Section: Introductionmentioning
confidence: 85%
“…On the contrary, other studies found an initial reduction of AD use during the peak of the first wave followed by an increased use in the subsequent periods [21]. Finally, some authors reported a non-significant change in psychotropic medication dispensing, including ADs, during the outbreak [22]. To the best of our knowledge, evidence on the impact of lockdowns on AD use in Italy is still scant and deserves careful evaluation.…”
Section: Introductionmentioning
confidence: 85%
“…Despite two studies showing an increase in the delivery of psychotropic drugs during the COVID-19 pandemic, our study had an exhaustive sample size ( 24 ) and a long-term follow-up ( 25 ). On the opposite, some studies did not find significant variation in the prescription of psychotropic drugs following the pandemic ( 26 30 ) that may be explained by specificities of the lockdown in each country. For example, Sweden, ( 30 ) Poland, ( 26 ) or Northern California ( 29 ) showed only an isolated peak in March 2020.…”
Section: Discussionmentioning
confidence: 97%
“…On the opposite, some studies did not find significant variation in the prescription of psychotropic drugs following the pandemic ( 26 30 ) that may be explained by specificities of the lockdown in each country. For example, Sweden, ( 30 ) Poland, ( 26 ) or Northern California ( 29 ) showed only an isolated peak in March 2020. The discordance of results between countries may be explained by difference in the severity of lockdown restrictions, with a variable impact on daily life.…”
Section: Discussionmentioning
confidence: 97%
“…The lack of significance in the combined sex group (albeit exhibiting a non-significant trend in the same direction) reduce confidence in this association. Furthermore, downstream effects from the 2020 onset of the Covid-19 pandemic 24 has been hypothesized to increase mental health problems in youth, potentially influencing suicide death rates. The present study evinced no such effects in males or females for the year 2020 compared to 2016-2019.…”
Section: Discussionmentioning
confidence: 99%
“…Variables not satisfying requirements for normal distribution were subjected to transformation by Blom's method 29 for the subsequent robust linear regression analyses (but not for nonparametric tests, i.e., the Wilcoxon rank sum exact test). To examine potential confound conferred from the 2020 onset of the Covid-19 pandemic 24 , we implemented the Wilcoxon Rank Sum Exact test to compare the mean of min-max normalized values for excess adolescents suicide death rates over 2016-2019 with values in the year 2020 across the 21 regionsevincing no significant difference in any sex group (combined sexes: p-value = 0.811, females: p-value = 0.613, males: p-value = 0.358). Multiple ordinary least squares regression was implemented to examine the relative contribution of each treatment modality to the mean clozapine/ECT/lithium proxy variable.…”
Section: Discussionmentioning
confidence: 99%